Environmental DNA and its role in identifying yeast biodiversity in mangrove ecosystem: A literature review - Kusuma Rahayu Lila; Retnaningsih Soeprobowati Tri; Warsito Budi (E3S Web of Conferences)
Yeast biodiversity in mangrove ecosystems is crucial for their health and ecological functions. However, traditional methods often fail to detect yeast species that are difficult to culture or slow growing, leaving a significant portion of this biodiversity undetected. This study explores the use of environmental DNA (eDNA) as an alternative method for identifying yeast species in mangrove ecosystems, addressing data gaps left by conventional methods. Data is collected from various relevant literature sources, including scientific journals, books, and research reports. The literature review reveals that eDNA analysis can improve conservation management by providing robust biodiversity assessments. Future research should focus on understanding eDNA persistence, ecological implications, and improving bioinformatics for better data interpretation. In-depth long-term studies are recommended to study the temporal and spatial dynamics of yeast communities in mangrove ecosystems. Further validation of the eDNA method in various environmental conditions is needed to ensure reliability. Research on yeast interactions with other ecosystem components and the impact of human activities like pollution and habitat change is also important.